Survey of VO2 Max Smoker and Non-Smoker Levels in High School Students - Cita Putra, Yasir Valdi (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2018)
Cigarette lovers in the country of Indonesia quite a lot. As commonly known, smoking can affect the respiratory system of the body and VO2 Max. The problem in the study is how the level of VO2 Max in the students of smokers and non-smokers in MA Negeri Pagerbarang Tegal regency. The purpose of the study was to determine the level of VO2 Max students smokers and non-smokers in MA Negeri Pagerbarang Tegal regency. The type and design of the study were surveys. The population of all male students of class X and XI MAN Pagerbarang, amounted to 91 students and consists of 8 classes. The sample was taken by Total Sampling technique. The level of VO2 Max is measured by Multistage Fitness Test. Results of the study with questionnaires, as many as 21 students are non-smokers, 21 students are moderate smokers and 43 are light smokers. Results of the study with the MFT instrument, average VO2 Max light smoker students were 42.97 ml / kg / min, moderate smokers at 38.71 ml / kg / min, and not smokers 49.33 ml / kg / min. Based on the results of research and discussion description, it can be concluded that there are indications of non-smoker students have a good level of ability VO2 Max good, light smoker s are moderate, and moderate smokers are moderate. Students should avoid or stop smoking, because smoking can have a negative impact, especially for the respiratory system and the level of VO2 Max.